Efektivitas Monitoring dan Evaluasi dalam Implementasi Kebijakan Pendidikan : Pendekatan dan Tantangan - Mela Safitri Situmorang; Aulia Sari Damanik; Tengku Darmansyah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The purpose of writing this article is to find out in full about the Effectiveness of Monitoring and Evaluation in the Implementation of Educational Policy approaches and challenges. This article is compiled by means of a literature study using qualitative research methods. Monitoring and evaluation (M&E) of educational policy is a systematic process used to measure, monitor, and assess the implementation of educational policies and their impact on predetermined objectives. Monitoring and evaluation (M&E) plays an important role in ensuring the success of educational policy implementation. This article examines the main approaches used in M&E of educational policies and the challenges faced in the process. This article provides strategic recommendations for improving the effectiveness of M&E in the educational context, so that policies can produce significant and sustainable impacts.